Sustainable growth rate, optimal growth rate, and optimal payout ratio: A joint optimization approach - Chen, Hong-Yi; Gupta, Manak C.; Lee, Alice C.; Lee, Cheng-Few (Journal of Banking & Finance, 2013)
This study investigates the investment decision and dividend policy jointly from a non-steady state to a steady state. We extend Higgins, 1977, Higgins, 1981, Higgins, 2008 sustainable growth rate model and develop a dynamic model which jointly optimizes the growth rate and payout ratio. We optimize the firm value to obtain the optimal growth rate in terms of a logistic equation and find that the steady state growth rate can be used as the benchmark for the mean-reverting process of the optimal growth rate. We also investigate the specification error of the mean and variance of dividend per share when introducing the stochastic growth rate. Empirical results support the mean-reverting process of the growth rate and the importance of covariance between the profitability and the growth rate in determining dividend payouts. The intertemporal behavior of the covariance may shed some light on the fact of disappearing dividends over decades.